Efektivitas Edukasi Audiovisual Dan Role Play Terhadap Kesiapsiagaan Bencana Gempa Bumi Pada Anak SD Negeri 1 Banda Sakti Kota Lhokseumawe - Pohan, Adli Kurniawan; Ikhsan, Maulana; Putri, Baluqia Iskandar (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Indonesia is a country prone to natural disasters, one of which is earthquakes, as exemplified by the devastating earthquake in Aceh in 2004. The high number of casualties resulting from earthquakes is often attributed to a low level of preparedness knowledge. Therefore, providing earthquake preparedness education should ideally start within the school environment. The delivery of this education also requires appropriate and effective methods to ensure that the knowledge imparted is remembered and applied effectively. These methods include audio, visual, audiovisual, and role play. This study aims to assess the effectiveness of earthquake preparedness education using audiovisual and role play methods among students of SD Negeri 1 Banda Sakti, Lhokseumawe City. This research falls under the category of quasi-experimental research, with a total of 71 respondents. The sample was selected using total sampling. The research findings indicate that before receiving education, the majority of respondents had a low level of preparedness. After the education, the preparedness level of the respondents increased to a high category, and there was an improvement in the average posttest results for both the audiovisual and role play groups. Data analysis was conducted using the Wilcoxon test and independent T-test, with the statistical results showing a p-value less than 0.05. Based on the research findings, it can be concluded that providing education through audiovisual media and role play significantly influences preparedness for earthquake disasters among students at SD Negeri 1 Banda Sakti, Lhokseumawe. Additionally, there is a significant difference in effectiveness between audiovisual media and role play, with role play being considered more effective than audiovisual media.